Mapping the Anticancer Mechanism of Asiatic Acid : A systematic review of preclinical evidence - Sari, Rina Kartika; Dalimunthe, Rahmi Syaflida; Amir, Lisa Rinanda; Wimardhani, Yuniardini Septorini; Musfiroh, Ida; Sastradipura, Dewi Fatma Suniarti (Indonesian Journal of Pharmaceutical Science and Technology, 2026)
Studies have demonstrated that Asiatic acid (AA) from Centella asiatica has anticancer properties in cancer cell lines, but translating these findings into clinical research remains challenging. This review aims to provide a robust scientific foundation for enhancing the translational potential of AA-based anticancer therapy. The PubMed, Scopus, and ScienceDirect databases were searched electronically using specific keywords and screened in accordance with the PRISMA 2020 guidelines.  Fourteen studies meet the criteria. All research was conducted in vitro; four studies were conducted both in vitro and in vivo, and three were conducted in silico.Asiatic acid (AA) demonstrates potent anticancer activity by modulating key signaling pathways, including PI3K/Akt and NF-κB, thereby inhibiting proliferation, promoting apoptosis, and reducing metastasis. Its cytotoxic effects are time- and dose-dependent (1–50 µM) and minimal in normal cells. While AA and its derivatives consistently outperform controls, limitations such as missing control dose data warrant further investigation. Future studies should focus on in vivo validation, clinical translation, and advanced strategies such as targeted delivery and AI-assisted drug development to fully realize AA’s therapeutic potential.